“Green” Synthesis of Metallic Nanoparticles by Sonoelectrochemical and Sonogalvanic Replacement Methods - Оrest Kuntyi; Galyna Zozulya; Andriy Kytsya (Bioinorganic Chemistry and Applications)
The main features of the “green” synthesis of metallic nanoparticles (MNPs) by the sonoelectrochemical methods are manufacturability, environmental friendliness, and the possibility of controlling the geometry of the forming particles. The electrochemical reduction technique allows efficiently designing the metal nanoparticles and provides the control of the content of components of bimetallic nanoparticles, as well as minimizing the number of precursors in working solutions. Due to the generation of turbulence, microjets, and shock waves, ultrasound increases mass transfer and formation of radicals in aqueous solutions and, accordingly, accelerates the processes of nucleation and growth of MNPs. Therefore, this hybrid method, which combines electrolysis and ultrasound, has attracted the interest of researchers in the last two decades as one of the most promising techniques. The present work presents a short analysis of the reference literature on sonoelectrochemical synthesis of metallic and bimetallic nanoparticles. The main factors influencing the geometry of nanoparticles and their size distribution are analyzed. The use of pulsed ultrasound and pulsed current supply during sonoelectrochemical synthesis is especially effective in designing MNPs. Emphasis is placed on the role of surfactants in the formation of MNPs and sacrificial anodes in providing the algorithm: “anodic dissolution-electrochemical reduction of metal-nucleation and formation of МNPs.” It is noted that ultrasound allows synthesizing the MNPs and M1M2NPs during the galvanic replacement, and an analogy of the formation of nanoparticles by sonogalvanic replacement and sonoelectrochemical method is shown.